A View to Margin on Average in Colombia (2014)
During the last decades the mediation margin of the bank companies in Colombia appears as one of the highest levels in comparison with the region countries, for that reason exist the need to evaluate its importance, emphasizing which are the factors that intervene and the decisions that the public policies have taken in benefit of the economic society. Therefore there are analyzed the tools that the Republic Bank uses and its influence in the generation of profit on the part of the shareholders of the banks: likewise it’s important to analyze the rate of bank intermediation through this one could be perceived which is the real aim of the public monetary policies and who are the beneficiaries of the changes in the increase of it them appraises that they shape (Rate of capture and rate of placement).